The role of size in PEGylated liposomal doxorubicin biodistribution and anti‐tumour activity - Saba Dadpour; Amin Mehrabian; Mahdieh Arabsalmani; Elaheh Mirhadi; Anis Askarizadeh; Mohammad Mashreghi; Mahmoud Reza Jaafari (IET Nanobiotechnology)
Abstract The size of nanoliposome‐encapsulated drugs significantly affects their therapeutic efficacy, biodistribution, targeting ability, and toxicity profile for the cancer treatment. In the present study, the biodistribution and anti‐tumoral activity of PEGylated liposomal Doxorubicin (PLD) formulations with different sizes were investigated. First, 100, 200, and 400 nm PLDs were prepared by remote loading procedure and characterised for their size, zeta potential, encapsulation efficacy, and release properties. Then, in vitro cellular uptake and cytotoxicity were studied by flow cytometry and MTT assay, and compared with commercially available PLD Caelyx®. In vivo studies were applied on BALB/c mice bearing C26 colon carcinoma. The cytotoxicity and cellular uptake tests did not demonstrate any statistically significant differences between PLDs. The biodistribution results showed that Caelyx® and 100 nm liposomal formulations had the most doxorubicin (Dox) accumulation in the tumour tissue and, as a result, considerably suppressed tumour growth compared with 200 and 400 nm PLDs. In contrast, larger nanoparticles (200 and 400 nm formulations) had more accumulation in the liver and spleen. This study revealed that 90 nm Caelyx® biodistribution profile led to the stronger anti‐tumour activity of the drug and hence significant survival extension, and showed the importance of vesicle size in the targeting of nanoparticles to the tumour microenvironment for the treatment of cancer.